Monetary Policy and the Lost Decade : Lessons from Japan - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2009)
This paper investigates how monetary policy can help ward off a protracted deflationary slump when policy rates are near the zero bound by studying the experience of Japan during the "Lost Decade" which followed the asset-price bubble collapse in the early 1990s. Estimation results based on a structural model suggest that the Bank of Japan's interest-rate policy fits a conventional forward-looking reaction function with an inflation target of about 1 percent. The disappointing economic performance thus seems primarily due to a series of adverse economic shocks rather than an extraordinary policy error. In addition, counterfactual policy simulations based on the estimated structural model suggest that simply raising the inflation target would not have yielded a lasting improvement in performance. However, a price-targeting rule or a policy rule that combined a higher inflation target with a more aggressive response to output would have achieved superior stabilization results.